Utilization of the Kedu Ex-Residency Museum (Place where the Prince was captured Diponegoro) as a source for Learning History - Raharjo, Yoel Kurniawan; Kurniawan, Hendra; Hadi, Florentinus Suryanto (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to describe how the use of the former Kedu Residency Museum, where Prince Diponegoro was captured by General De Kock, became a source of learning local history in history subjects at SMAN 4 Magelang. The research method used is qualitative with a descriptive approach. The data collection techniques include direct observation in museums and schools, in-depth interviews with museologists and history teachers, as well as museum and school documentation. The results of the research show: (1) the Former Kedu Residency Museum is the site of a historical event where Diponegoro was tricked and arrested by General De Kock through negotiations, (2) the Former Kedu Residency Museum is a cultural heritage building protected by the state, (3) History Teacher at SMAN 4 Magelang have used this museum as a local history learning laboratory, (4) The Museum Tour Learning Model is used by history teachers to provide students with direct experience learning local history.